Original articleHigh fructose solution induces neuronal loss in the nucleus of the solitary tract of rats - Rafati, Ali; Anvari, Enaiat; Noorafshan, Ali (Folia Neuropathologica, 2013)
Nucleus tractus solitarius (NTS) is the main region for the cardiovascular regulation including the baroreceptor reflex. Although the physiological and biochemical aspects of a high fructose diet on the brain have been studied, its effects on the quantitative aspects of the NTS have received less attention. The objective of the present study was to quantify the structural changes in the NTS after the consumption of high fructose solution, using stereological methods. Male rats were distributed randomly into two groups. One group received fructose (10%) in tap water for six weeks and the other one received tap water without fructose. The total volume of the NTS and number of the neurons of the nucleus were estimated using stereological methods including Cavalieri and disector methods. The coefficient of error (CE) of the estimators was calculated. Fasting plasma concentrations of glucose, triglyceride, cholesterol and insulin were obtained. Also a glucose tolerance test was done. The results showed no significant changes in glucose, triglyceride, cholesterol and insulin concentrations between the two groups. The glucose tolerance test did not show any differences, either. The mean (coefficient of variation) volume of the NTS and the neuronal number was 0.68 (0.2) mm3 and 68000 (0.13) in the control rats, respectively. But the volume of the NTS and total number of the neurons decreased by 41% in the fructose-treated group (p ≤ 0.01). Consumption of high fructose solution for six weeks led to a decrement in the volume and number of the neurons in the NTS in rats.